1979
DOI: 10.2754/avb197948010019
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Vitamins A, E and Carotene in Cows in Late Pregnancy and in Their Foetuses

Abstract: Jagoi P .• J. Bouda. J. Geryk: The Plasma LefJeZs of Vitamin A. E and Carotene in Cows in Late Pregnancy and in Their Foetuses. Acta vet. Brno. 48.1979: 19-23. Experiments involving 20 cows in late pregnancy and their foteuses aged 8-9 months were conducted to study the blood plasma content of the vitamins A. E and carotene and the liver vitamin A content of these individuals.The vitamin A content of the foetal plasma wss more than two times lower than that of the dams. and the foetal liver content of vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Sufficient intake of vitamin E through colostrum is extremely important for newborn ruminants, because fat-soluble vitamins are transported only in a limited degree through the placenta into the foetus and therefore the stores of the newborn calves are low (Van Saun et al, 1989;Njeru et al, 1994). Analysis of Jagos et al (1979) show, that the concentrations of β-carotene, as well as of vitamin A and E in the blood plasma of foetuses in the age of 8 to 9 months are much lower than that in the plasma of their cows. Figures 3 and 4 show the results of additional examinations of colostrum.…”
Section: Resultsmentioning
confidence: 99%
“…Sufficient intake of vitamin E through colostrum is extremely important for newborn ruminants, because fat-soluble vitamins are transported only in a limited degree through the placenta into the foetus and therefore the stores of the newborn calves are low (Van Saun et al, 1989;Njeru et al, 1994). Analysis of Jagos et al (1979) show, that the concentrations of β-carotene, as well as of vitamin A and E in the blood plasma of foetuses in the age of 8 to 9 months are much lower than that in the plasma of their cows. Figures 3 and 4 show the results of additional examinations of colostrum.…”
Section: Resultsmentioning
confidence: 99%
“…Levels of vitamin E and β-carotene were found to be between 7.38 and 4.31 mg/mL at the beginning of pregnancy, whereas they were between 1.14 and 1.64 mg/mL at the final stages of pregnancy (Aksakal et al 1990). In the same way, vitamin E levels in the blood serum of Holstein cows were determined as 1.37 mg/mL during the sixth and seventh months of pregnancy (Jagos et al 1979), whereas in the last month of pregnancy the vitamin E content had decreased to 1.68 mg/mL (Lynch 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of vitamin A and ß-carotene in blood and especially in liver of newborn offspring are very low [37,38] . It has been reported that these levels increase with colostrums intake [17][18][19]38,39] and especially there is a positive correlation between mother, colostrums and calf for ß-carotene [40] .…”
Section: Days Because Of High Levels Of Vitamin a In Colostrums (224mentioning
confidence: 99%